2017
DOI: 10.1021/acs.langmuir.7b02810
|View full text |Cite
|
Sign up to set email alerts
|

Association Behavior of Poly(ethylene oxide)–Poly(propylene oxide) Alternating Multiblock Copolymers in Water toward Thermally Induced Phase Separation

Abstract: Thermal changes in the association behavior of poly(ethylene oxide)-poly(propylene oxide) alternating multiblock (PEO-PPO AMB) copolymers in water are investigated by the use of transmittance and light scattering measurements. Two PEO-PPO AMB copolymers with a different weight fraction of PEO, (EOPO) and (EOPO), are prepared. The weight-average molecular weights of (EOPO) and (EOPO) estimated by static light scattering measurements are 1.3 × 10 and 4.1 × 10 g mol, respectively. The number of PEO-PPO repeating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 30 publications
1
22
0
Order By: Relevance
“…The intercept of the solid line in the inset gives a value of 39 , which corresponds to the T θ of the system. In previous papers, we reported that the micellization temperature of EO 220 PO 33 6 is around 41-50 20 and the second virial coefficient, A 2 , of EO 220 PO 33 8 approaches zero around 50 23 . The results shown here imply that the Shultz-Flory theory is applicable even to PEO-PPO AMB copolymers.…”
Section: Molecular Weight Dependence Of T C For the Peo-ppomentioning
confidence: 90%
See 3 more Smart Citations
“…The intercept of the solid line in the inset gives a value of 39 , which corresponds to the T θ of the system. In previous papers, we reported that the micellization temperature of EO 220 PO 33 6 is around 41-50 20 and the second virial coefficient, A 2 , of EO 220 PO 33 8 approaches zero around 50 23 . The results shown here imply that the Shultz-Flory theory is applicable even to PEO-PPO AMB copolymers.…”
Section: Molecular Weight Dependence Of T C For the Peo-ppomentioning
confidence: 90%
“…The PEO-PPO AMB copolymer was prepared by a dehydrated condensation reaction according to the literature 23 . Briefly, α,ω-diamino PPO JEFFAMINE D-2000; weight-average molecular weight M w 2,000 was kindly supplied by Huntsman Corporation.…”
Section: Experimental Procedures 21 Preparation Of Peo-ppo Amb Copolmentioning
confidence: 99%
See 2 more Smart Citations
“…21 As a result, A 2 of PEO− PNiPAm AMB copolymers systematically changes depending upon the stereoregularity of the PNiPAm block. A 2 of 3−5 × 10 −6 L mol g −2 has been reported for (EO 220 PO 33 ) 8 and (EO 68 PO 33 ) 9 (PEO−PPO AMB copolymers) in water at 25 °C, 16 which is larger by 10 times than that for AMBm45. That is, (EO 220 PO 33 ) 8 and (EO 68 PO 33 ) 9 chains are more repulsive in water than AMBm45.…”
Section: ■ Experimental Methodsmentioning
confidence: 92%